2017
DOI: 10.1016/j.jpainsymman.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Symptom Clusters Identified Using Ratings of Symptom Occurrence vs. Severity in Lung Cancer Patients Receiving Chemotherapy

Abstract: Context An important question in symptom clusters research is whether the number and types of symptom clusters vary based on the specific dimension of the symptom experience used to create the clusters. Objectives Given that lung cancer patients undergoing chemotherapy (CTX) report an average of 14 co-occurring symptoms and studies of symptom clusters in these patients are limited, the purpose of this study, in lung cancer patients undergoing CTX (n=145), was to identify whether the number and types of sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 51 publications
(72 reference statements)
10
51
0
Order By: Relevance
“…The most common and severe symptom was lack of energy and the most distressing symptom was ''I don't look like myself.'' Consistent with previous reports in patients with breast 19,34,35 and lung 36 cancer, for all three symptom dimensions, the same four symptom clusters (i.e., psychological, CTXrelated, GI, weight change) were identified and the symptoms within each cluster were relatively similar. The remainder of this discussion will place these findings within the context of the extant literature.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The most common and severe symptom was lack of energy and the most distressing symptom was ''I don't look like myself.'' Consistent with previous reports in patients with breast 19,34,35 and lung 36 cancer, for all three symptom dimensions, the same four symptom clusters (i.e., psychological, CTXrelated, GI, weight change) were identified and the symptoms within each cluster were relatively similar. The remainder of this discussion will place these findings within the context of the extant literature.…”
Section: Discussionsupporting
confidence: 89%
“…Although a psychological symptom cluster was reported in previous studies of patients with breast, 19,35,37 lung, 36,38 and heterogeneous cancer diagnoses, 16,39e44 it was found in only three of the six studies of symptom clusters in patients with GI cancers. 11,13,14 Across the four symptom cluster studies in GI cancers (i.e., our study and the other three 11,13,14 ), anxiety and depression were the two consistent symptoms.…”
Section: Psychological Symptom Clustermentioning
confidence: 80%
See 1 more Smart Citation
“…This could miscategorise participants who may have a higher occurrence rate but lower severity rates, and the symptom burden could be overestimated. However, the authors found similarities in both the number and types of symptom clusters in patient with breast, lung and paediatric cancer undergoing active treatment (Baggott, Cooper, Marina, Matthay, & Miaskowski, 2012; Ward Sullivan et al., 2017; Wong et al., 2017). Until now, there has been no gold standard recommendation for LCA in symptom analysis.…”
Section: Discussionmentioning
confidence: 99%
“…New analyses with different samples and statistical approaches would be necessary before making such an important decision. In addition, it would be interesting to examine where symptoms recently added by some authors would be located in the continuum of the construct 31 (e.g., increased appetite, weight gain, abdominal cramps, and hot flashes).…”
Section: Discussionmentioning
confidence: 99%